PENGARUH DUE PROFESSIONAL CARE, MOTIVASI AUDITOR, TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT - Atiqoh, Nur; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test (a) the influence of due professional care to the audit quality, (b) the influence of auditor motivation to the audit quality, and (c) the influence of time budget pressure to the audit quality. The respondents are 60 auditors which are in the office and have not done field duties in BPK RI East Java Province yet. The sample collection technique has been done by using purposive sampling. The data has been processed by using the consideration of respondent which have position as partner, junior, and audit senior which has the position at least 1 years of service. The analysis technique has been done by using multiple linear regressions. The result of the research shows that Due Professional care has positive influence to the audit quality. It indicates that when the level of due professional care has been owned by auditors is getting higher; the result of audit inspection of the financial statement is getting high as well. The auditor motivation has positive influence to the audit quality. It indicates that high motivation can increase the confidence of an auditor, so it can generate qualified financial audit statement. The time budget pressure has positive influence to the audit quality. It indicates that when the time budget pressure which is owned by an auditor is getting better, the audit quality which will be generated is getting better as well.Keywords: Due Professional Care, Auditor Motivation, Time Budget Pressure, Audit Quality.